Green-synthesis of CuO and Ce-doped CuO nanoparticles using aqueous extract of yam peel and their antimicrobial properties - Mercy C. Ogwuegbu; Olalekan C. Olatunde; Trust M. Pfukwa; Doctor M.N. Mthiyane; Olaniyi A. Fawole; Damian C. Onwudiwe (Hybrid Advances)
The rise of drug-resistant microbes presents a critical global health challenge in the 21st century, necessitating the development of potent antimicrobial agents with broad-spectrum activity. Therefore, in this study, we explored the antimicrobial activity of copper oxide (CuO) and cerium-doped CuO (Ce-doped CuO) obtained through a facile green synthesis approach. The nanoparticles were synthesized using aqueous extract of Dioscorea spp (yam peel) and characterized for their physicochemical properties using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), electron microscopy, and UV–Vis spectroscopy. Their antimicrobial efficacy was tested against three bacterial strains—Enterococcus faecalis, Escherichia coli, and Listeria monocytogenes—and three fungal strains—Aspergillus niger, Mucor mucedo, and Penicillium chrysogenum. The results demonstrated that cerium doping significantly altered the physicochemical properties of CuO, leading to enhanced antimicrobial activity. The antibacterial zone of inhibition ranged from 7.50 to 16.55 mm for CuO and 11.80–19.50 mm for Ce-doped CuO. For antifungal activity, the minimum inhibitory concentration (MIC) ranged from 0.25 to 0.30 mg/mL for CuO and 0.025–0.03 mg/mL for Ce-doped CuO. Notably, the Ce-doped CuO nanoparticles exhibited antimicrobial effects comparable to standard antibiotics. These findings highlight the potential of green-synthesized Ce-doped CuO nanoparticles as effective antimicrobial agents. By leveraging green synthesis and elemental doping, this study offers a promising solution to combat a wide spectrum of infectious pathogens.